THE ACCOUNTING ROLE OF PUBLIC SECTOR MANAGEMENT IN SUPPORTING GOOD GOVERNANCE - Maria Yesika Silvi Pradipta; LMS Kristiyanti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
Public sector organizations are synonymous with government or business entities to perform public services. Management accounting is a field of accounting whose focus is to help management make plans for logical economic goals and make decisions. This research aims to find out how public sector management accounting plays a supporting role good governance. This research is a qualitative descriptive research, with research methods whose data sources come from literature studies, namely from various references. The research results obtained are based on various studies that public sector management accounting, with its various tasks in terms of planning, budgeting, control and evaluation, plays an important role in realizing good governance (good governance), which includes the principles of accountability, transparency, effectiveness and efficiency. Keywords: management accounting, good governance, public sector.